Wing shape of four new bee fossils (Hymenoptera: Anthophila) provides insights to bee evolution. - Manuel Dehon (Public Library of Science (PLoS), 2014)
Bees (Anthophila) are one of the major groups of angiosperm-pollinating insects and accordingly are widely studied in both basic and applied research, for which it is essential to have a clear understanding of their phylogeny, and evolutionary history. Direct evidence of bee evolutionary history has been hindered by a dearth of available fossils needed to determine the timing and tempo of their diversification, as well as episodes of extinction. Here we describe four new compression fossils of bees from three different deposits (Miocene of la Cerdanya, Spain; Oligocene of Céreste, France; and Eocene of the Green River Formation, U.S.A.). We assess the similarity of the forewing shape of the new fossils with extant and fossil taxa using geometric morphometrics analyses. Predictive discriminant analyses show that three fossils share similar forewing shapes with the Apidae [one of uncertain tribal placement and perhaps near Euglossini, one definitive bumble bee (Bombini), and one digger bee (Anthophorini)], while one fossil is more similar to the Andrenidae. The corbiculate fossils are described as Euglossopteryx biesmeijeri De Meulemeester, Michez, & Engel, gen. nov. sp. nov. (type species of Euglossopteryx Dehon & Engel, n. gen.) and Bombus cerdanyensis Dehon, De Meulemeester, & Engel, sp. nov. They provide new information on the distribution and timing of particular corbiculate groups, most notably the extension into North America of possible Eocene-Oligocene cooling-induced extinctions. Protohabropoda pauli De Meulemeester & Michez, gen. nov. sp. nov. (type species of Protohabropoda Dehon & Engel, n. gen.) reinforces previous hypotheses of anthophorine evolution in terms of ecological shifts by the Oligocene from tropical to mesic or xeric habitats. Lastly, a new fossil of the Andreninae, Andrena antoinei Michez & De Meulemeester, sp. nov., further documents the presence of the today widespread genus Andrena Fabricius in the Late Oligocene of France.